Effects of combined MAO-B inhibitors and levodopa vs. monotherapy in Parkinson’s disease - Krishna, Rakhee; Ali, Manal; Moustafa, Ahmed A. (Frontiers in Aging Neuroscience, 2014)
Background: Prior studies report that monoamine oxidases inhibitors (MAO-I) when used as an adjunct to levodopa ameliorate motor symptoms in Parkinson’s disease (PD), but this was not tested in relation to cognitive or psychiatric measures. Objective: Here, we tested the effects of MAO-I as an adjunct to levodopa, in comparison to levodopa or dopamine (DA) agonists alone, on various cognitive, affective and quality of life measures. Methods: We studied three groups of subjects: Healthy controls, PD patients on combined levodopa and MAO-I, and PD patients on levodopa or DA agonists only. Results: We found that compared to monotherapy, combined MAO-I and levodopa seemed to improve cognition, including probabilistic learning, working memory and executive functions. There were no differences between the different medication regimes on deterministic learning, attention or memory recall. It was also found that MAO-I as an adjunct to levodopa improves affective measures such as depression, apathy, anxiety and quality of life. Interestingly, this enhancing effect of combined levodopa and MAO-I was more pronounced in PD patients with severe akinesia, compared to patients with severe tremor. Conclusion: Our data are in agreement with (a) the Continuous Dopaminergic Stimulation (CDS) theory which states that continuous stimulation of the basal ganglia enhances motor, psychiatric and cognitive functions in PD patients and/or (b) findings that MAO-I increase the bioavailability of monoamines that have beneficial effects on motor and behavioral dysfunction in PD.